MODEL PEMBERDAYAAN MASYARAKAT UNTUK MENCEGAH KEKERASAN DALAM RUMAH TANGGA - Sigit Sanyata; Siti Rohmah Nurhayati; Kartika Nur Fathiyah (Jurnal Penelitian Humaniora, 2011)
The aim of this research is to produce a model of social empowerement to restrain domestic violence. As the first target is to identify understanding, necessity and design society empowerment model as mean to restrain domestic violence. This research, as the first year step, used research and development approach. The participans engaged in this research are 150 people spread in Bantul, Yogyakarta, and Kulonprogo. Sixty people are socialites as FGD subjects and 90 people were determined to fill in questionaire. FGD guide has been arranged to expose society’s potentials whilst the questionaire was to identify society understanding abouut domestic violence. Qualitative data were analyst descriptively and the quantitative were analyst descriptive-quantitatively. The results of the analysis are 1) society understanding of domestic violence still at cognitive level. 2) society has a comprehension that domestic violence could be prevented through society participations. 3) people need a model of domestic violence prevention. 4) tho odel of society empowerement is focused on optimalization of human, natural and social resources. The effort of empowerment has been done in three steps; increasing people awareness, capaciting and empowering.